School-to-work experiences: curriculum as a bridge. - Bonds BG (American Annals of the Deaf, 2003)
Because workers must be prepared to constantly update their skills and reeducate themselves for new skills, lifelong learning must be a goal for every teacher and student. The curriculum provided during educational experiences should pave the way for attainment of this goal. This is particularly true for deaf and hard of hearing students. School-to-work (STW) has become an umbrella term for activities, experiences and opportunities that prepare students for the world of work, such as youth apprenticeships, mentoring, internships, job shadowing, career exploration, and integration of academic and vocational curriculum. This article provides historical background on STW, laws shaping requirements for STW programs, and research supporting STW components. Recommendations are provided for curricular elements of an STW program, and trends in STW are forecast.